A Study Of Physical Conditions And Nutritional Status Of Football Schools In Sido Rukun Village Tebo District Jambi Province - Maliki, Aditya Imam; hastria Efendi,; wilda welis,; Ridho Bahtra , (Jurnal IKEOR, 2025)
This research is seen fron the results of researh in the village of Sido Rukun, Rimbo Ulu District, Tebo Regency, that the physical condition and nutritional status studies of the Football School Athletes are categorized as good. Flexiometer used (Flexiometer), agility used the Illinois Agility Run Test and the Endurance test used VO2Max, while to measure the nutritional status of athletes using BMI/U anthropometric standards for assessing nutritional status. This study used this research as a descriptive study using a quantitativ approah by collecting data using tests. This research will be carried out in the Sido Rukun Village Football School (SSB) field from March to April 2023, the populaton in theis studiy is 25 athletes while The samplyng technigue uses a tootal samplingg technique to collect a sample of 25 SSB athletes in Sido Rukun Village . Data analysis techniques using descriptive statistical analysis using frequency tabulation techniques or percentage techniques. Based on the analysis of nutritional status data in this study, it shows that there are 25 pillars of children with a percentage of 100% in the category of good nutrition according to the Anthropometric Standards while for physical condition tests there are still many results that are not optimal. Keywords: Study of Physical Conditions, Nutritional Status.